ANALISIS TERHADAP TINGKAT KREDIT MACET (NON PERFORMING LOANS) STUDI PADA BANK UMUM KONVENSIONAL PERIODE 2010-2014 - Rahmadani, Dianti (Jurnal Ilmiah Mahasiswa FEB, 2016)
The aim of this study is to analyze the bank-specific factors and macroeconomic factors that affecting the bank non-performing loans (NPL) is the size of banks, capital adequacy ratio (CAR), loan to deposit ratio (LDR), gross domestic product (GDP) and inflation. The method used is descriptive with secondary data from financial statements 5 banks as the object of research units. The data analysis technique is a panel regression, hypothesis testing when using a t-test to test the effect of partial variables and F-test to test the effect of variables simultaneously with a significant level of 5%. Based on these results concluded that partial bank size, LDR and GDP significant effect on the NPL. While CAR and inflation is not significant effect on the NPL. Simultaneously, all the independent variables significantly influence the level of influence of the NPL. Keywords : NPL, BANK SIZE, LDR, CAR, GDP, INFLATION